Integrating Traditional Games in Learning for Students' Interests and Motor Skills - Komaini, Anton; Inarta, Gian Utomo; Kiram, Phil Yanuar; Handayani, Sri Gusti (Jurnal Pendidikan dan Pengajaran, 2024)
This research is motivated by the importance of developing effective learning media in increasing students' interest and motor skills, especially in rural areas. This study aims to test students' responses to e-modules based on local wisdom treasure games, as well as to see the influence of the e-modules on students' interest and motor skills before and after their use. This type of research is development research using the ADDIE model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were 35 children in the interior village of Mentawai who were selected using random sampling techniques. The instruments used include observation sheets to measure students' responses to e-modules, as well as observation sheets to measure students' gross motor skills, both using the Likert scale. The data was analyzed with a T test to see the difference before and after the use of the e-module, as well as a correlation test to see the relationship between variables. The results showed that there was a significant difference in students' motor skills before and after using the e-module, as well as a significant difference in students' interest before and after using the e-module. The correlation test showed a very close relationship between students' response to the e-module and their motor skills, and between students' learning interests and motor skills. The conclusion of this study is that e-modules based on local wisdom games are effective in increasing students' interest and motor skills, with the implication that this e-module can be a useful learning medium to be applied more widely in rural areas.